KAJIAN MULTIKULTURALISME : IDE-IDE IMAJINER DALAM PEMBANGUNAN PUJA MANDALA - Ida Bagus Wika Krishna (Sekolah Tinggi Agama Hindu Negeri Mpu Kuturan Singaraja, 2019)
As a place of worship visited and involving multicultural communities, certainly there are imaginary ideas in terms of its creation, with the formation of the Mandala Puja there will be culture and implications involved there. Puja Mandala is a place of worship as well as a place for international tourism, there is an ideology in the process of formation in the form of political ideas, tourism ideas, and religious ideas. The political idea that is in the form of a goal to create a comprehensive national development of the Menparpostel Joop Ave, the idea of tourism that occurred in the formation of the Mandala Puja is to advance the economy of the surrounding community while at the same time forming a developing tourism area in Nusa Dua Bali, religious ideas contained in the formation of Puja Mandala namely the aim to increase internal harmony among religious communities, between religious communities, as well as between religious communities and the government.